ANALISIS DAMPAK ALIH FUNGSI LAHAN PERTANIAN TERHADAP PENDAPATAN PETANI DI KABUPATEN MIMIKA - Evatul Casanova Noviyanti; Irwan Sutrisno (JURNAL KRITIS (Kebijakan, Riset, dan Inovasi), 2021)
This study aims to determine whether or not there is a difference in income before and after that is obtained by farmer who change lan functions. This research uses comparative research methods. The data collection technique was carried out by means of observation, interviews, and open questionnaires. The data analysis instrument used paired sample t-test analysis. The results showed that farmer who changed land function, namely: before the land conversion was Rp. 28,109,863 and income after land conversion was Rp. 34,906,863. Then the farmer income increased to be higher after converting the land.